STRATEGI INDONESIA MENINGKATKAN EKSPOR SARANG BURUNG WALET KE TAIWAN TAHUN 2017-2019 - Novi Wulandari; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research describes about Indonesia's strategy in increasing exports of swallow’s nest to Taiwan , which is experiencing an increasing demand due to the return of the principle to functional food. Bird’s nest is made from bird saliva which is considered very beneficial for helath. Swallow’s nest is usually used in making soup and also as an ingredient in medicene.most of the swallow’s nests produced by Indonesia are exported to other countries, one of which is Taiwan.Indonesia and Taiwan have signed many cooperation agreements, both in the economic and socio-cultural fields. One of the coorporation agreements was the signing of the MoU on Morotai Development Project as a follow-up to thw signing of the Letter Of Intent (LOI).The writer collects data from books, academic journals, official documents, theses and sources from the internet related to research issues regarding strategy in increasing exports of swallow’s nest to Taiwan. The writer uses the perspective of liberalism and the level of analysis of the nation state. While the theory used in this theory is the theory of international cooperation. This reserach finds that optimal efforts from the government together with Indonesian stakeholders are needed to be able to increase Indonesian exports of swallow’s nest to Taiwan while bird’s nest export opportunities in Taiwan are still very wide open Keywords: Requets, Agreement, Increase, Export, Swallow’s nest